Digital Marketing Perspectives in E-Commerce (European Journal of Economics, Finance and Business Development, 2023)
This article explores the dynamic landscape of digital marketing within the realm of e-commerce, shedding light on the evolving strategies and perspectives that drive success in the online marketplace. From the integration of cutting-edge technologies to the harnessing of data analytics, this study delves into key aspects that define the contemporary digital marketing landscape in e-commerce. Through a comprehensive analysis, the article aims to provide insights into effective approaches, challenges, and future trends shaping the intersection of digital marketing and e-commerce.